p21CIP1 promotes mammary cancer initiating cells via activation of Wnt/TCF1/CyclinD1 signaling - Benard, Outhiriaradjou (Mol Cancer Res, 2019)
Cancer stem cells (CSCs) generate and sustain tumors due to tumor initiating potential, resulting in recurrence or metastasis. We showed that knockout of the cell cycle inhibitor, p21CIP1, in the PyMT mammary tumor model, inhibits metastasis; however the mechanism remained unknown. Here, we show a pivotal role for p21 in potentiating a cancer stem-like phenotype. p21 knockout in PyMT mammary tumor cells caused dramatic suppression of cancer stem cell properties involving tumorsphere formation, ALDH1 activity, and tumor initiating potential, which were in turn rescued by p21 overexpression into PyMT/p21 knockout cells. Interestingly, p21 knockout dramatically suppresses Wnt/β-catenin signaling as shown by striking inhibition of Wnt3a-stimulated expression of LEF1 and TCF1 transcription factors. TCF1 knockdown in PyMT cells suppressed tumorsphere formation due to Cyclin D1 attenuation. These data demonstrate that p21 promotes a cancer stem cell like phenotype via activation of Wnt/TCF1/Cyclin D1 signaling. Implication: p21 is a strong promoter of mammary cancer stem cells.